Plan estratégico para el mejoramiento de los servicios educativos de la unidad educativa ¨Pucayacu¨ cantón La Maná período 2015 - 2019 - Cunuhay Pilatasig, Sandro Stalin (2015)
Educational Unit "Pucayacu" Canton La Maná, Cotopaxi Province, Parish Pucayacu in the unique specialty of Agriculture, aimed at training high school with ethical principles established under the conditions of the law of ministry of education that can participate competent criticism responsible and successful in economic, political and social and cultural life of our county. Inserting educated in the practice of moral and civic and off campus that oriented work constitutes an opportunity to improve the quality of life of the community ethical values. Thus transforming the quality of public education has several meanings and implications. On the one hand, it is a process of long-term change; which has the same core set of practices (principals, teachers, students, parents, supervisors and support staff). Moreover, transform school management involves the development of new practices, create and strengthen ways to improve the efficiency, equity, relevance and significance of educational action of the canton La Manna. In the present study suggests the need to conduct research on the quality of education, allowing raise within the framework of a strategic planning process for the continuous improvement of education.